IMPROVING THE COGNITIVE ASPECT OF CHILDREN AGED 5-6 THROUGH NUMERAL LITERACY - Erna Budiarti; Rini Kurniawati; Lilis Amperawati; Rustatik Rustatik; Andriani Andriani; Cahyani Setiawati (Jurnal Scientia, 2022)
There are 6 kinds of basic literacy that must be introduced to early childhood, one of which is numeracy literacy. Numerical literacy for early childhood is not only introducing numbers or number symbols, but numerical literacy is the basis for the ability to be able to solve problems in everyday life. The research was conducted by stimulating literacy skills, especially symbols or number symbols through activities to introduce the concept of addition and subtraction. The purpose of this study was to determine the effect of numeracy literacy on cognitive improvement in early childhood. The research method used is descriptive qualitative, with the research subjects being group B children (aged 5-6 years) at RA Raudhatul Ummah Mustikajaya Bekasi City. The object under study is the child's cognitive ability. Data collection through tests and interviews. The results showed that children's cognitive abilities increased significantly through numeracy literacy.